KAJIAN NILAI TAMBAH DAN STRATEGI PENGEMBANGAN AGRIBISNIS PEMINDANGAN IKAN LAUT DI KECAMATAN AMBULU - Amien Pudjanarso (RELASI : JURNAL EKONOMI, 2012)
Prevered fish produced is one of much popular processing product has the market demand/ consumer’s receipment. This study aimed to evaluate Prevered Fish production from value added, cost efficiency and business development strategy perspectives- SWOT analysis. The analysis used in this study is descriptive analysis, value added, benefit cost ratio and SWOT analysis. The results show that prevered fish are positive value to value added from processing, the results of benefit cost ratio more than one value and SWOT evaluation has position on opportunity – weakness. The business development strategy of prevered fish must be improved on the internal management business.